PENERAPAN QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) UNTUK PENENTUAN ALTERNATIF STRATEGI PADA STIE MALANGKUÃEÃWARA MALANG - Maria, Evi (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: The objective of this research is to examine strategy formulation and implementation at STIE MalangkuÃ§eÃ§wara, through the internal and external factors that influence universities competition changing. Moreover, it is to find out strategy alternative using QSPM method. Method of this study is case study. Internal and external factors that used by STIE MalangkuÃ§eÃ§wara have changed, that is why a newÂ formulation is needed. The research used IFE and EFE matrix, TOWS matrix, IE matrix and QSPM matrix that resulted vary strategies for STIE MalangkuÃ§eÃ§wara. Based on QSPM method, market penetration should be implemented by STIE MalangkuÃ§eÃ§wara, because it has highest score that able to make the organization stable and increase the market . Moreover, based on internal factor strategy, the shorter period for graduates to acquire the first occupation, indicates graduates have good quality. As a consequence, stakeholderâs trust is very high. Keywords : IFE, EFE, TOWS, QSPM.